Proceedings of the Specialists' Meeting on Acoustic/Ultrasonic Detection of in Sodium Water Leaks on Steam Generators, 1 - 3 October 1990, held in Aix-En-Provence, France - The Specialists' Meeting on Acoustic/Ultrasonic Detection of in Sodium Water Leaks on Steam Generators (1990 : France); Cea, Girard; International Atomic Energy Agency ([France] : IAEA, 1990)
05